2013
DOI: 10.1186/1471-2148-13-240
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary analysis of hydrophobin gene family in two wood-degrading basidiomycetes, Phlebia brevispora and Heterobasidion annosum s.l.

Abstract: BackgroundHydrophobins are small secreted cysteine-rich proteins that play diverse roles during different phases of fungal life cycle. In basidiomycetes, hydrophobin-encoding genes often form large multigene families with up to 40 members. The evolutionary forces driving hydrophobin gene expansion and diversification in basidiomycetes are poorly understood. The functional roles of individual genes within such gene families also remain unclear. The relationship between the hydrophobin gene number, the genome si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 49 publications
5
20
0
Order By: Relevance
“…In contrast, class I hydrophobins reside in all four quadrants of the plot displaying, as expected, comparatively high sequence variability7. In PC2, however, there is a distinct separation of Ascomycota and Basidiomycota Class I sequences, with an intermediate region containing sequences originating from both phyla consistent with previous phylogenies171834. The mixed-region of Class I contains all previously structurally characterized Class I hydrophobins and has little sequence or loop length conservation, an observation consistent with the current description of the Class I group of hydrophobins in the literature11.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast, class I hydrophobins reside in all four quadrants of the plot displaying, as expected, comparatively high sequence variability7. In PC2, however, there is a distinct separation of Ascomycota and Basidiomycota Class I sequences, with an intermediate region containing sequences originating from both phyla consistent with previous phylogenies171834. The mixed-region of Class I contains all previously structurally characterized Class I hydrophobins and has little sequence or loop length conservation, an observation consistent with the current description of the Class I group of hydrophobins in the literature11.…”
Section: Resultssupporting
confidence: 81%
“…While putative Class II hydrophobins are still readily identified by sequence analysis, it remains difficult to reach a single consensus as to a Class I signature, leading to the proposition for further subdivision of the class141516. Considering phylogenetic analyses of sequences from a wide range of fungi, bootstrap values support a separation of Class I ascomycota and basidiomycota sequences but are too low to confidently support further subdivisions1718. It is also important to note that while the number of predicted sequences increases, both the forces driving hydrophobin gene evolution and the roles of individual genes remain largely unclear18.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is predicted to be secreted, the sequence is less than 300 amino acids, and it contains many cysteines. Such proteins have been studied recently in Phlebia brevispora and Heterobasidion annosum (29). The authors focused their analysis on hydrophobins.…”
Section: Transcriptomic Analysis (I) Overview Of Gene Expressionmentioning
confidence: 99%
“…In H. annosum s.s, a conifer pathogen with a similar life history to Ps , 16 hydrophobin-encoding genes with different regulatory patterns were observed. Several were highly up-regulated during saprotrophic growth on bark, sapwood and/or heartwood of Scots pine, suggesting that this pathogen employs different hydrophobins during growth on diverse wood components [25]. A separate study found that two H. annosum hydrophobin genes are up-regulated in aerial hyphae but are down-regulated during early infection of pine seedling roots [26].…”
Section: Discussionmentioning
confidence: 99%